Development of a new analytical spectroscopic methodology based on the competitive aggregation in a dye–surfactant–drug system: Application to the determination of gemfibrozil. Issue 4 (2008) - Amjadi Amjadi, Mohammad Mohammad; Manzoori Manzoori, Jamshid L. Jamshid L.; Farzampour Farzampour, Leila Leila
Abstract : A new analytical methodology based on the competitive aggregation in a dye–surfactant–drug system is developed for the determination of gemfibrozil. Eriochrome Blue Black R (EBBR) and Didodecyldimethylammonium bromide (DDABr) were the dye and surfactant used, respectively. In the proposed method, the anions of the dye bind to the cationic surfactant molecules to form dye–surfactant aggregates, which are monitored from changes in UV-Vis absorption features of the dye. In the ternary EBBR–DDABr–drug mixtures, the drug competes with the dye to interact with the surfactant, which results in a decrease in dye–surfactant aggregates formation. This, again, causes a change in absorption properties of the dye. The measurement parameter is the difference between the absorption of the dye in the presence and absence of the drug. In the appropriate experimental conditions the absorbance differences are directly proportional to the drug concentration. The influence of several experimental variables such as pH, concentrations of buffer, EBBR and DDABr on the measurement parameter were studied. Under the optimum conditions, the calibration graph was linear up to 6.0 μg ml −1 with the correlation coefficient of 0.998. The limit of detection and quantification were found to be 0.044 and 0.15 μg ml −1, respectively. The method was validated and applied to the determination of gemfibrozil in pharmaceutical preparations.